STRATEGIES OF SCIENCE TEACHERS IN OVERCOMING THE FACTORS THAT CAUSE LEARNING DIFFICULTIES - Siti Bustani Fauziah; Fitri Nur Mahmudah (International Journal of Educational Management and Innovation, 2020)
During the learning process, there are still many students who have difficulty learning, it can make students do not like science learning and students feel bored with the way the teacher teaches. As a result, grades in science lessons are still low. The teacher has an important role in overcoming the factors that cause learning difficulties. The purpose of this study is 1) to identify the science teacher's strategy in overcoming the factors that cause learning difficulties, 2) to describe the teacher's steps in implementing strategies to overcome the factors causing learning difficulties, 3) to identify the results of applying the strategy in overcoming the factors causes of learning difficulties. His research is qualitative research with a descriptive approach. The data were collected by interviewing and observing with science teachers and documentation. The collected data were analyzed using the analysis interactive model which includes data collection, data display, and verification. The results showed that 1) the strategies used were cooperative and inquiry 2) the steps implemented by the science teacher through a cooperative strategy consist of 10 steps, whereas for the inquiry strategy consists of 8 steps, 3) The results of the application of cooperative and inquiry strategies are that students become more motivated in learning, have collaboration between groups, understanding related to science subjects increases, do not get bored quickly, are creative, active, science learning outcomes increase, and critical thinking in solving problems.